Insights into reproductive dynamics and feeding biology of Sphyraena putnamae Jordan and Seale, 1905 exploited in the Indian EEZ: stock dynamics of Sphyraena putnamae - R. Vinothkumar; Subal Kumar Roul; Ajay D. Nakhawa; H. M. Manas; S. Surya; C. Anulekshmi; Shubhadeep Ghosh; K. M. Rajesh; A. Margaret Muthu Rathinam; E. M. Abdussamad; Prathiba Rohit (Indian Journal of Fisheries, 2024)
The sawtooth barracuda Sphyraena putnamae, widely distributed in the Indo-Pacific region, is one of the commercially important barracuda species exploited by trawls in the Indian EEZ. The present study examined 2,135 S. putnamae collected during 2014-2020 from different fish landing centres along the Indian coast, to elucidate their reproductive and feeding behaviour. The fork length of sampled females and males varied from 12.5 to 130.9 cm and 16.5 to 90.0 cm respectively. Negative allometric growth was observed with a significant difference (p<0.05) between the sexes. The observed sex ratio (Female:Male) was 1.23:1, indicating the dominance of females. Size at sexual maturity for females and males were estimated at 55.3 and 45.4 cm fork length respectively. The higher proportion of spawning capable individuals and higher gonadosomatic index (GSI) values in females observed during March to May and November-December revealed the bimodal and protracted spawning nature of this species. Absolute fecundity increased with fork length and weight and varied from 70,080 to 10,18,068 oocytes with an average of 3,16,568 oocytes. The stomach vacuity index of females and males was 49.09 and 47.92% respectively. Fifty-nine prey items were identified in the diet, with a predominance of fishes confirming S. putnamae has a piscivorous feeding behaviour. Keywords: Management, Protracted spawners, Piscivore, Sawtooth barracuda, Sex ratio